Pengolahan Air Bersih Dengan Metode Filtrasi Sederhana di RW 02 Desa Cipangeran Kecamatan Saguling - Sindi Sapitri; Aziz, Diar Abdul; Afiatika, Yulia (PROCEEDINGS UIN SUNAN GUNUNG DJATI BANDUNG, 2024)
RW 02 One of the communities in West Bandung Regency without access to clean water is Cipangeran Village. Cipangeran village gets harder to clean because of its placement in a hill valley that gets drier in the summer. It is said that the soil contains a lot of lime, which causes collected water to turn hard when it enters homes. Because living things require water of a certain quality, amount, and availability, the presence of contaminated water will also affect the life of those living things. Therefore, a method for making the local water usable is required. By working diligently to increase locals’ awareness of basic filtration devices made of materials found nearby, specifically charcoal and gravel. As well as other fibers, coconut. One technique that is frequently employed is the filtering process. Natural resources are secure and generally simple to get. The use of charcoal and gravel as an absorbent will significantly aid filtering. The porous nature of the absorbent is one of its qualities. Gravel and carbon from charcoal are some of these. According to Caroline, hazardous chemicals like metal 3 can be absorbed by activated carbon. In order to remove odors and colors from water, activated carbon is very helpful. According to the activity’s findings, the locals were quite enthusiastic and had a positive reaction to the activities. This is due to the fact that after passing through a straightforward filtering procedure, water that was previously unclean and unfit for use becomes clean and suitable for use. Residents of RW 02 can use as much clean water as possible without having to purchase it in this manner. Due to the simplicity of locating the necessary materials in the immediate area, the filtering procedure that was described to the villagers is equally simple to comprehend and implement in village life. Keywords: Filtration, Cipangeran, service, KKN, Program, Community